Early prescriptions of antibiotics and the risk of allergic disease in adults: a cohort study. Issue 1 (23rd December 2003) - Cullinan, P; Harris, J; Mills, P; Moffat, S; White, C; Figg, J; Moon, A; Newman Taylor, A J
Abstract : Background: It is frequently asserted that antibiotic prescriptions in childhood are associated with the development of allergic disease, especially asthma. A study was undertaken to establish the direction of this relationship. Methods: A retrospective cohort study of 746 adults was performed in three general practices. Antibiotic prescriptions in the first 5years of life, collected from contemporary medical records, were related to self-reports of asthma and hay fever and the results of skin prick testing with common aeroallergens. Results: There was no relationship between early antibiotic prescription and atopy, either for all antibiotic use (OR 1.01) or for antibiotics prescribed at different ages. The significant associations between prescriptions at ages 4 and 5 and hay fever (OR 1.23 and 1.16, respectively) were explained by coexisting asthma. Relationships between antibiotic use and asthma (allergic or otherwise) were statistically significant and strengthened with increasing age of prescription, but were largely confined to antibiotics prescribed for lower respiratory symptoms. Conclusions: The reported associations between childhood antibiotic use and asthma are most plausibly explained by "reverse causation"—the tendency for prescriptions to be written for the early manifestations of pre-existing asthma.